The S–O–R Perspective Through the Mediation of Perceived Value in Shaping Reuse Intention - Muhammad Zaky Nurrahman; Yolanda Masnita; Kurniawati Kurniawati (Majapahit Journal of Islamic Finance and Management, 2026)
The fast-food industry increasingly deploys Self-Service Technologies (SSTs) to enhance operational efficiency. However, sustaining user retention remains challenging, compounded by a recent theoretical anomaly where traditional Service Quality failed to predict usage intention in automated contexts. Addressing this gap, this study re-evaluates the Stimulus-Organism-Response (S-O-R) framework by replacing the insignificant Service Quality variable with System Quality and integrating Perceived Value as a mediator. Analyzing data from 221 respondents using PLS-SEM, results reveal that technical stimuli—specifically System Quality and Design Quality—significantly enhance Perceived Value (R2=0.783), which subsequently acts as a dominant mediator in shaping Reuse Intention (R2=0.585). Theoretically, this resolves the "service paradox" in developing economies, confirming that technical reliability replaces traditional service attributes. Practically, managers must prioritize zero-error stability, as consumers perceive technical efficiency as the primary utility driving sustainable reuse behavior.